Alteration of melatonin secretion in patients with type 2 diabetes and proliferative diabetic retinopathy - Hikichi T (Dove Medical Press, 2011)
Taiichi Hikichi1, Naohiro Tateda2, Toshiaki Miura31Department of Ophthalmology, Ohtsuka Eye Hospital, Sapporo; 2Asahikawa National College of Technology, Asahikawa; 3Faculty of Pharmaceutical Sciences, Hokkaido University, Sapporo, JapanBackground: The purpose of this study was to evaluate the dynamics of plasma melatonin secretion in patients with type 2 diabetes mellitus and diabetic retinopathy.Methods: Plasma melatonin levels were measured by high-performance liquid chromatography in 56 patients. Patients were divided into a diabetic group (30 patients) and a nondiabetic group (26 patients). The diabetic group was divided further into a proliferative diabetic retinopathy (PDR) group (n = 14) and a nonproliferative diabetic retinopathy (NPDR) group (n = 16). Plasma melatonin levels obtained at midnight and 3 am were compared between the groups.Results: Nighttime melatonin levels were significantly lower in the diabetic group than in the nondiabetic group (P < 0.03) and lower in the PDR group than in the nondiabetic and NPDR groups (P < 0.01 and P < 0.03, respectively), but no significant difference was found between the nondiabetic and NPDR groups. The daytime melatonin level did not significantly differ between the nondiabetic and diabetic groups or between the nondiabetic, NPDR, and PDR groups.Conclusion: The nighttime melatonin level is altered in patients with diabetes and PDR but not in diabetic patients without PDR. Although patients with PDR may have various dysfunctions that affect melatonin secretion more severely, advanced dysfunction of retinal light perception may cause altered melatonin secretion. Alteration of melatonin secretion may accelerate further occurrence of complications in diabetic patients.Keywords: circadian rhythm, diabetes, proliferative diabetic retinopathy, melatonin